MODEL MANAJEMEN LAYANAN TEKNOLOGI INFORMASI BERBASIS ITIL VERSI 3 DI LLDIKTI WILAYAH II - Retnawiyati, Eka; Antoni, Darius; Herdiansyah, M Izman (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2021)
The development of information technology has provided convenience in every service to service users. Region II Higher Education Service Institutions in accordance with Permendikbud Number 34 of 2020 have the task of facilitating the improvement of the quality of higher education implementation with higher education work areas in South Sumatra Province, Lampung Province, Bengkulu Province and Bangka Belitung Islands Province. LLDIKTI Region II already has online-based services such as the Lecturer Rank Information System (SIKITO) and DiTES as well as the LLDIKTI Region II website. In addition to online-based services, LLDIKTI has unystematic public services such as Institutional Services, Administrative Personnel Services and Lecturers. These services have not been integrated with each other. Information Technology Service Management (ITSM) is the planning and control of information technology assets such as systems, infrastructure, people and processes to support business operational needs as efficiently as possible to ensure that organizations have the ability to evaluate processes and performance on an ongoing basis in order to identify and implement opportunities for improvement ( opportunities for improvement). IT service management planning to identify Service documents that exist in LLDIKTI Region II and plan information technology service documentation with ITIL version 3. Information Technology Services are useful for aligning business with service quality and determining customer needs and expectations in an agreement between service providers and service users .